Transmission biology of maize striate mosaic virus, its vector and host plant range and impacts on maize - Vilanova, Euclides de Sousa (2025)
Maize striate mosaic virus (MSMV) is a new member of the genus Mastrevirus (family Geminiviridae) recently reported in maize (Zea mays L.) and in the corn leafhopper, Dalbulus maidis (DeLong & Wolcott) (Hemiptera: Cicadellidae), suggesting its potential role as a vector. Assuming that vector type and transmission mode are stable traits at the virus genus level, it is hypothesized that D. maidis transmits MSMV in a persistent, non-propagative manner, as observed for other mastreviruses. This study aimed to: (i) test the hypothesis that D. maidis is a vector of MSMV; (ii) characterize MSMV transmission by D. maidis in terms of persistence, minimum latency period (LPmin), and efficiency in relation to acquisition access period (AAP) and inoculation access period (IAP), and specificity; (iii) evaluate host susceptibility and MSMV pathogenicity in maize; and (iv) assess the impacts of mixed viral infections on pathogenicity and transmission. The results confirmed MSMV transmission by D. maidis and the association of the virus infection with mottling and chlorotic streak symptoms. The temporal characteristics of transmission were consistent with a persistent and non-propagative vector- virus relationship. Transmission occurred after short access periods to the plants (1 h), and efficiency increased with longer AAP and IAP durations. The LPmin of the virus in the vector was short (4h or less). Leafhoppers retained transmission ability for several days, ranging from 68 days or 1012 days after a 48-h AAP by nymphs or adults, respectively, and up to 1216 days when both stages were jointly submitted to a 96-h AAP. However, both transmission rates and virus detection in insects declined over time. When acquisition occurred during the nymphal stage, the virus remained detectable after molting. These results provide indirect evidence that MSMV circulates within the vector without replication, leading to a progressive loss of viral titer after acquisition. Planthopper species and the corn aphid, Rhopalosiphum maidis (Fitch), were able to acquire MSMV, but only the leafhoppers Agallia albidula Uhler and Planicephalus flavicosta (Stål) transmitted it, indicating the specificity of transmission by leafhoppers. New MSMV host plants were identified, including sugarcane, Brachiaria grass, gamba grass, and pearl millet, with transmission mediated by D. maidis; only sugarcane showed symptoms, which were characterized by foliar chlorotic stripes. Evaluation of pathogenicity in different maize genotypes revealed variable symptom expression, ranging from asymptomatic or mild symptoms with minor or no damage, to severe symptoms associated with high losses in grain yield. Coinfection of MSMV with maize yellow mosaic virus (MaYMV, genus Polerovirus, family Solemoviridae) did not intensify impacts compared to single infections. In contrast, mixed infection of MSMV with sugarcane mosaic virus (SCMV, genus Potyvirus, family Potyviridae) exacerbated SCMV-associated impacts in certain genotypes. Furthermore, prior SCMV infection in test plants significantly increased MSMV transmission by D. maidis, whereas prior MSMV infection had no effect on SCMV transmission by R. maidis. The transmission of both viruses by their respective vectors was not significantly influenced by mixed infection in the source plant. Therefore, this study provides fundamental insights into the biology and ecology of MSMV transmission and highlights its potential relevance in maize, with important implications for the management of this pathosystem.